Discourses in place : language in the material world - Scollon, Ronald, 1939- (Routledge, 2003)
Publisher description: Explores how the physical and material characteristics of language in the world give meaning to communication. Ron and Suzanne Scollon argue that we can only interpret the meaning of public texts like road signs, notices and brand logos by considering the world and culture that surrounds them. Drawing on a wide range of real examples, from signs in the Chinese mountains to urban centers in Europe, Asia and America, the book equips students with the methodology and models they need to undertake their own research in "geosemiotics," this key interface between semiotics and intercultural communication. Includes a "how to use this book" section, group and individual activities and a glossary of main terms.